Sonography of the canine healthy and diseased spleen - BHADWAL, M S; MIRAKHUR, K K (The Indian Journal of Animal Sciences, 2013)
There was negate information on the modalilty of choice for imaging spleen, therefore present study was undertaken to arrive at a suitable imaging protocol and elucidate ultrasonographic spleen in normal and sick dogs, Spleen was scanned ultrasonographically in 20 healthy and 6 sick dogs, Normal spleen was seen as superficial structure cranial to the left kidney. Splenomegaly and architectural changes were sonographically discernable in sick dogs.